COMPREHENSIVE FRAMEWORK FOR REHABILITATION: SOCIAL, LEGAL, AND ECONOMIC PERSPECTIVES IN INDONESIA : ISBN 978-630-95064-0-5 - Sumarno, Setyo (Technium Books, 2024)
The book: COMPREHENSIVE FRAMEWORK FOR REHABILITATION: SOCIAL, LEGAL, AND ECONOMIC PERSPECTIVES IN INDONESIA ISBN 978-630-95064-0-5 is published in Technium Books. Authors full list: Setyo Sumarno, Mu’man Nuryana, Nurhayu, Togiaratua Nainggolan, Achmadi Jayaputra, Sugiyanto, Ruaida Murni, Ery Agus Kurnianto, Himawan Estu Bagijo, Sulistyani Eka Lestari, Mohamad Miftah, Asriani, Herrukmi Septa Rinawati, Andjar Prasetyo, Andi Tenri Awaru, Husnah Rahman, Hasniati